Computing the monodromy and pole order filtration on Milnor fiber cohomology of plane curves. (March 2019) - Dimca, Alexandru; Sticlaru, Gabriel
Abstract: We describe an algorithm computing the monodromy and the pole order filtration on the Milnor fiber cohomology of any reduced projective plane curve C . The relation to the zero set of Bernstein–Sato polynomial of the defining homogeneous polynomial for C is also discussed. When C has some non-weighted homogeneous singularities, then we have to assume that a conjecture holds in order to get some of our results. In all the examples computed so far this conjecture holds.